Systematic screening for right-to-left shunt prior to lead extraction. (19th May 2022) - Breitenstein, A; Hofer, D; Starck, CH; Steffel, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Transvenous lead extraction has become a relevant treatment option in patients with device-associated infection, but also in the context of device- and lead dysfunction. Lead extraction can be complicated by a stroke, which may result from paradoxical embolization of lead debrids during lead extraction in the presence of a patent foramen ovale (PFO) with a right-to-left shunt. Purpose: Analysis of the presence of a PFO in patients undergoing transvenous lead extraction in a Swiss tertiary centre. Furthermore, different strategies to reduce the risk for stroke due to the presence of a PFO will be summarized. Methods and Results: In this retrospective analysis from January 2017 until December 2021, a total of 304 patients who underwent lead extraction were included. In nearly half of the population, lead dysfunction was the leading cause for extraction, while device-associated infection was present in 31 % of the patients. In 14 patients (4.6 %), a right-to-left shunt was detected either during (via transesophageal echocardiography) or prior to the procedure. Prior to the systematic pre-procedural PFO screening, 9 patients with a right-to-left shunt were identified of which 2 patients suffered from a peri-interventional stroke (22 %) while in the population without a PFO no stroke occurred. The remaining 5 patients with a right-to-left shunt were identified prior to the lead extraction procedure (after setting up an institutional PFO screening programm) and were treated accordingly. Since then, no further neurological episodes occurred (Figure 1). If a PFO was identified, an interventional PFO occlusion was performed either prior to the lead extraction (2 of 5 patients) or together with the lead extraction as a single procedure (1 patient). In the 2 other patients, where a device infection was present together with a PFO, the PFO shunt was occluded transiently using a sizing balloon during the lead extraction procedure to avoid to implant a PFO occluder device in an infectious environment. Conclusions: Presence of a right-to-left shunt in patients who need to undergo transvenous lead extraction is a known risk factor for embolic strokes. Identification and treatment of this condition prior or during lead extraction is associated with a reduction in stroke events.